Damage Propagation at the Interface of a Sandwich Beam - Hammoudi, Imane; Touati, Mokhtar; Chabaat, Mohamed (Periodica Polytechnica Civil Engineering, 2022)
In this research work, damage propagation at the interface of a cracked sandwich beam is considered. The behavior of Sandwich Beams (SB) depends upon a law based on relationship between tangential or normal efforts with inelastic propagation. As the crack propagates; fracture parameters such as stress intensity factors and energy release rates corresponding to the applied shear stress in mode I and II are determined. Linear and nonlinear models are presented. It is shown that the Timoshenko beam’s theory is employed in the formulation of transverse shear and peel stresses at the overlap ends. These parameters are used to derive energy release rates. Besides, effects of the adhesive thickness and shear modulus on the shear and peel stresses in the adhesive are studied. Obtained results from the analytical solution for the case of a sandwich beam at the interface (adhesive part) agree well with numerical investigations available in the literature. It is also proven that the contribution of the adhesive bond to the energy release rate increases for softer adhesives, shorter cracks and thicker bonds.